Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 6 - Factoring, Solving Equations, and Problem Solving - Chapter 6 Review Problem Set - Page 273: 9



Work Step by Step

The given expression can be written as $=(x^2)^2-1^2$ The binomial above is a difference of two squares. RECALL: $a^2-b^2=(a-b)(a+b)$ Factor the difference of two squares using the formula above with $a=x^2$ and $b=1$ to obtain: $=(x^2-1)(x^2+1)$ Factor the first binomial (a difference of two squares) using the formula above with $a=x$ and $b=1$ to obtain: $=(x-1)(x+1)(x^2+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.